"Seat of the soul"? The structure and function of the pineal gland in women with alleged spirit possession—Results of two experimental studies. Issue 7 (7th June 2020) - Bastos, Marco Aurélio Vinhosa; Bastos, Paulo Roberto Haidamus de Oliveira; e Paez, Loyná Euá Flores; de Souza, Edna Oliveira; Bogo, Danielle; Perdomo, Renata Trentin; Portella, Renata Boschi; Ozaki, Jorge Guilherme Okanobo; Iandoli, Décio; Lucchetti, Giancarlo
Abstract: Background: Cultural traditions attribute to pineal gland an important role for spiritual experiences. Mediumship and spirit possession are cultural phenomena found worldwide which have been described as having dissociative and psychotic‐like characteristics, but with nonpathological aspects. A sympathetic activation pattern in response to spirit possession has been reported in some studies, but empirical data on pineal gland is scarce in this context. Methods: We aimed to investigate pineal gland and pituitary volumes, as well as urinary 6‐sulfatoxymelatonin levels in 16 alleged mediums (Medium Group‐MG) compared with 16 healthy nonmedium controls (Control Group) (Experiment 1). Furthermore, we aimed to evaluate urinary 6‐sulfatoxymelatonin and stress reactivity in GM ( n  = 10) under different physiological conditions (Experiment 2). Results: In Experiment 1, MG presented higher scores of anomalous experiences, but there were no between‐group differences regarding mental health or subjective sleep quality. Similar pineal gland and pituitary volumes were observed between groups. There were no between‐group differences in urinary 6‐sulfatoxymelatonin collected under equivalent baseline conditions. In Experiment 2, the rise of anxiety and heart rate in response to mediumistic experience was intermediate between a nonstressful control task (reading) and a stressful control task (Trier Social Stress Test—TSST). No significant differences were observed in 6‐sulfatoxymelatonin urinary levels between the three conditions. The pattern of stress reactivity during the TSST was normal, but with an attenuated salivary cortisol response. Conclusion: The normal neuroimaging and stress reactivity findings in MG contrast with the abnormal results usually observed in subjects with psychotic and dissociative disorders. Abstract : Pineal and pituitary volumes similar in alleged mediums and nonmedium controls. Baseline 6‐sulfatoxymelatonin similar in alleged mediums and nonmedium controls. Subjective sleep quality similar in alleged mediums and nonmedium controls. Normal pattern of laboratory stress reactivity in alleged mediums. Results contrast to reports for with psychotic and dissociative disorders.